Adults with unilateral congenital ear canal atresia – sound localization ability and recognition of speech in competing speech in unaided condition. (1st July 2021) - Siegbahn, Malin; Engmér Berglin, Cecilia; Hultcrantz, Malou; Asp, Filip
Abstract: Background: Individuals with unilateral hearing loss show poor spatial hearing, but individual variability is high. Aims/objectives: To investigate if the degree of hearing loss in unilateral ear canal atresia affects horizontal sound localization and speech recognition. Materials and methods: Twelve subjects with unilateral ear canal atresia without childhood hearing intervention. Previously published data from eight normal-hearing subjects in normal binaural as well as experimentally induced unilateral hearing loss served as a reference. Horizontal sound localization and recognition of speech in spatially separate competing speech were assessed. Results: Linear regression analysis demonstrated a relationship between sound localization accuracy (SLA) and the air conduction pure tone average of the atretic ear ( r  = 0.85, p =.007). The large proportion of variability in SLA (72%) explained by the degree of hearing loss of the atretic ear indicates that binaural processing is possible. SLA was worse than for normal hearing individuals ( p <.0001), and comparable to moderate simulated unilateral hearing loss ( p =.13). Speech discrimination was significantly worse than normal ( p <.0001) and not dependent on degree of hearing loss of the atretic ear. Conclusions and significance: Individuals with congenital unilateral ear canal atresia show impaired horizontal SLA and recognition of speech in competing speech.